Optimal-Transport Analysis of Single-Cell Gene Expression Identifies Developmental Trajectories in Reprogramming - Schiebinger, Geoffrey; Shu, Jian; Tabaka, Marcin; Cleary, Brian; Subramanian, Vidya; Solomon, Aryeh; Gould, Joshua; Liu, Siyan; Lin, Stacie; Berube, Peter; Lee, Lia; Chen, Jenny; et al. (Cell, 2019)
Understanding the molecular programs that guide differentiation during development is a major challenge. Here, we introduce Waddington-OT, an approach for studying developmental time courses to infer ancestor-descendant fates and model the regulatory programs that underlie them. We apply the method to reconstruct the landscape of reprogramming from 315,000 single-cell RNA sequencing (scRNA-seq) profiles, collected at half-day intervals across 18 days. The results reveal a wider range of developmental programs than previously characterized. Cells gradually adopt either a terminal stromal state or a mesenchymal-to-epithelial transition state. The latter gives rise to populations related to pluripotent, extra-embryonic, and neural cells, with each harboring multiple finer subpopulations. The analysis predicts transcription factors and paracrine signals that affect fates and experiments validate that the TF Obox6 and the cytokine GDF9 enhance reprogramming efficiency. Our approach sheds light on the process and outcome of reprogramming and provides a framework applicable to diverse temporal processes in biology. [Display omitted] •Optimal transport analysis recovers trajectories from 315,000 scRNA-seq profiles•Induced pluripotent stem cell reprogramming produces diverse developmental programs•Regulatory analysis identifies a series of TFs predictive of specific cell fates•Transcription factor Obox6 and cytokine GDF9 increase reprogramming efficiency Application of a new analytical approach to examine developmental trajectories of single cells offers insight into how paracrine interactions shape reprogramming.